2021
DOI: 10.1111/psyp.13830
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular function response to prolonged sitting combined with a high‐glycemic index meal: A double‐blind, randomized cross‐over trial

Abstract: Acute prolonged sitting leads to cerebrovascular disruptions. However, it is unclear how prolonged sitting interacts with other common behaviors, including high-(HGI) and low-glycemic index (LGI) meals. Using a double-blind randomized cross-over design, this study evaluated the effects of prolonged (3 hr) sitting, with a high-(HGI;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…Our results build upon those of Wanders, Cuijpers, et al [38] who found that after 4-h of sitting with different Western meal types, physical activity interruption delayed post-breakfast mood and vigour decrements, as well as increases in fatigue and sleepiness irrespective of meal type. However, our findings are also in direct conflict to others [3] who assessed the effects of a high and low glycaemic beverage on TMT B pre and post 180 min of uninterrupted sitting. The authors found that irrespective of the beverage type, completion time significantly improved over 180 min of sitting.…”
Section: Comparison To the Literaturecontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results build upon those of Wanders, Cuijpers, et al [38] who found that after 4-h of sitting with different Western meal types, physical activity interruption delayed post-breakfast mood and vigour decrements, as well as increases in fatigue and sleepiness irrespective of meal type. However, our findings are also in direct conflict to others [3] who assessed the effects of a high and low glycaemic beverage on TMT B pre and post 180 min of uninterrupted sitting. The authors found that irrespective of the beverage type, completion time significantly improved over 180 min of sitting.…”
Section: Comparison To the Literaturecontrasting
confidence: 99%
“…The differences in findings between this study and ours may be explained by the dissimilar protocols used. Burnet, Blackwell, et al [3] did not report TMT familiarisation prior to their experimental trials, whereas in the current study there was prior practise during the familiarization visit in order to try and remove any learning effect. Learning effects with the TMT have previously been reported.…”
Section: Comparison To the Literaturementioning
confidence: 81%
See 3 more Smart Citations